1984
DOI: 10.1159/000299081
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Unconjugated and Total Oestrogens and Dehydroepiandrosterone, Progesterone and Urinary Oestriol Excretion in Pre-Eclampsia

Abstract: Peripheral serum levels of unconjugated (E1 and total (tE1) oestrone, unconjugated oestradiol-17Β, unconjugated (E3) and total (tE3) oestriol, progesterone, unconjugated dehydroepiandrosterone (DHA) and dehydroepiandrosterone sulphate (DHAS), and urinary tE3 excretion were determined in pre-eclamptic patients at gestational weeks 32 and 36 and in women with normal pregnancy at the corresponding length of gestation. DHA and DHAS were also analyzed in sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…Women with preeclampsia, notably severe preeclampsia, have been reported to have lower estrogen levels during pregnancy (5,21). Some studies have also reported higher levels of androgens in women with preeclampsia (22), and low levels of androgens have been implicated in the pathogenesis of testicular cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Women with preeclampsia, notably severe preeclampsia, have been reported to have lower estrogen levels during pregnancy (5,21). Some studies have also reported higher levels of androgens in women with preeclampsia (22), and low levels of androgens have been implicated in the pathogenesis of testicular cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although the study subjects themselves measured some end point variables (weight, height, and waist and hip circumferences), it is highly unlikely that any possible measurement error differs by exposure status. Altered placental function is described in preeclampsia, and several hormonal factors that may relate preeclampsia to decreased risk of breast cancer have been reported: reduced levels of estrogens (19) and IGF-1 (20), and increased levels of progesterone (21) and androgens (19,22). These factors may influence the offspring through programming, which hypothetically would alter age at menarche or final height.…”
Section: Discussionmentioning
confidence: 99%
“…However, circulating maternal estrogens near delivery do not seem to be lower in preeclampsia compared with uncomplicated pregnancy (33,34). Alterations in estrogen conjugation in preeclampsia may explain why concentrations are reduced in urine (the conjugated form), but not in maternal serum (33,35). In addition, the limited data are not consistent with lower umbilical cord blood (from here on referred to as ''cord'') estriol, estradiol, and estrone concentrations in preeclampsia (36).…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%